Air pollution exposure and its effects on idiopathic pulmonary fibrosis: clinical worsening, lung function decline, and radiological deterioration - Mariscal-Aguilar, Pablo; Gómez-Carrera, Luis; Bonilla, Gema; Díaz-Almirón, Mariana; Gayá, Francisco; Carpio, Carlos; Zamarrón, Ester; Fernández-Velilla, María; Torres, Isabel; Esteban, Isabel; Regojo, Rita; Villamañán, Elena; et al. (Frontiers in Public Health, 2024)
Major urban pollutants have a considerable influence on the natural history of lung disease. However, this effect is not well known in idiopathic pulmonary fibrosis (IPF).Aim: This study aimed to investigate the effects of air pollution on clinical worsening, lung function, and radiological deterioration in patients with IPF.Methods: This exploratory retrospective cohort study included 69 patients with IPF, monitored from 2011 to 2020. Data on air pollution levels, including carbon monoxide (CO), nitrogen dioxide (NO2), particulate matter ≤2.5 µM (PM2.5), ozone (O3), and nitrogen oxides (NOx), were collected from the nearest air quality monitoring stations (<3.5 km from the patients' homes). Patient outcomes such as clinical worsening, lung function decline, and radiological deterioration were assessed over various exposure periods (1, 3, 6, 12, and 36 months). The statistical analyses were adjusted for various factors, including age, sex, smoking status, and treatment.Results: There was an association between higher O3 levels and an increased likelihood of clinical worsening over 6 and 36 months of exposure (odds ratio [OR] and 95% confidence interval [